CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE OF MALAYSIAN PUBLIC LISTED MANUFACTURING FIRMS - Muhammad Afnan Aniq, Abdul Khalis; Norlina, Kadri; Nurul Syuhada, Zaidi; Bakri, Abdul Karim (UNIMAS Publisher, 2025)
This study examines how corporate governance mechanisms influence the financial performance of Malaysian public listed manufacturing firms between 2019 and 2023. Drawing on agency theory and stewardship theory, the analysis focuses on board size, leverage, liquidity, and revenue growth as determinants of return on assets (ROA). Secondary data from 20 manufacturing firms listed on Bursa Malaysia were analysed using panel regression models, including Pooled OLS, Random Effects, and Fixed Effects estimators. The results indicate that leverage exerts a statistically significant negative effect on ROA, while liquidity and revenue growth are positively associated with firm performance. Board size shows no significant relationship with ROA, suggesting that the effectiveness of the board depends more on its quality and expertise than its numerical size. The findings extend prior Malaysian and merging‑market evidence on governance–performance linkages and provide practical insights for policymakers, managers, and researchers interested in strengthening governance frameworks in the manufacturing sector.